1996
DOI: 10.1111/j.1399-3038.1996.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection: its role in aeroallergen sensitization during the first two years of life

Abstract: Our aim was to study the influence of infection with the respiratory syncytial virus (RSV) in non-hospitalized infants on sensitization to aeroallergens and the early manifestation of atopy. Six hundred and nine infants from the prospective German Multicenter Cohort Study on Atopy were included, 38% of whom had an elevated atopic risk. RSV IgG and IgM antibodies were tested by ELISA with gradient purified RSV antigen. Specific IgE against mites, cat dandruff, birch and grass pollens and relevant nutritional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 25 publications
(21 reference statements)
0
26
0
2
Order By: Relevance
“…From infancy on, the incidence of atopic dermatitis in our cohort was more frequent among children with first-degree relatives with the same phenotype. 21 In contrast, recurrent wheezing during the first 2 years of life was associated with serologic evidence of respiratory syncytial virus infection, 22 and thereafter, a positive family history of asthma became a risk factor. 21 In this study, the risk of both allergic sensitization and (more clear-cut after infancy) asthma symptoms was reduced in children with a higher vaccination coverage (Figs 2 and 3), suggesting that vaccinations may have a stronger impact on allergic than on nonallergic asthma.…”
Section: E286mentioning
confidence: 99%
“…From infancy on, the incidence of atopic dermatitis in our cohort was more frequent among children with first-degree relatives with the same phenotype. 21 In contrast, recurrent wheezing during the first 2 years of life was associated with serologic evidence of respiratory syncytial virus infection, 22 and thereafter, a positive family history of asthma became a risk factor. 21 In this study, the risk of both allergic sensitization and (more clear-cut after infancy) asthma symptoms was reduced in children with a higher vaccination coverage (Figs 2 and 3), suggesting that vaccinations may have a stronger impact on allergic than on nonallergic asthma.…”
Section: E286mentioning
confidence: 99%
“…Extensive literature describes human humoral immune responses to RSV (15)(16)(17)(18)(19) and MPV (5,19). Seropositivity usually develops during early childhood.…”
mentioning
confidence: 99%
“…A cohort study done by Foster et al also found that IgE, to common allergens, was more common after severe RSV infections in young children (Foster et al, 1996). Furthermore, RSV infection after 2 years of age did not play a role in sensitization against aeroallergens (Foster et al, 1996). This implies that RSV plays a pivotal role in influencing immune responses to allergens in young children.…”
Section: Mechanisms Of Rsv Induced Allergen Immunomodulationmentioning
confidence: 91%
“…Children who developed RSV, early in life, were more likely to produce IgE to common food and inhalant allergens such as egg white, cat, birch and mite (Sigurs et al, 1995). A cohort study done by Foster et al also found that IgE, to common allergens, was more common after severe RSV infections in young children (Foster et al, 1996). Furthermore, RSV infection after 2 years of age did not play a role in sensitization against aeroallergens (Foster et al, 1996).…”
Section: Mechanisms Of Rsv Induced Allergen Immunomodulationmentioning
confidence: 95%